ASTRONOMICAL CALIBRATION OF THE SERRAVALLIAN/TORTONIANCASE PELACANI SECTION (SICILY, ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
We performed a cyclostratigraphic study of a sedimentary sequence (Case Pelacani section) outcropping in the south-eastern margin of Sicily (Italy) and covering the Upper Serravallian/Lower Tortonian stratigraphic interval. Calcareous plankton biostratigraphic data reported in another paper proved that all the sequence of bio-events generally reported from just below and above the S/T boundary is present in the section. They allowed a detailed correlation with the Gibliscemi section.  Preliminary paleomagnetic data suggest that a secondary remagnetization  component prevents the recognition of the correct sequence of paleomagnetic chrons along the studied interval. The sedimentary record has been compared, on the basis of an integrated calcareous plankton biostratigraphy, with that of the Gibliscemi section. Cyclostratigraphic analysis of the lithological patterns recognized throughout the succession and the application of spectral methodologies to the abundance fluctuations of the planktonic foraminifer Globigerinoides quadrilobatus highlighted the presence in the signal of the classic Milankovitch frequencies (precession, obliquity and eccentricity). Correlation of the lithological patterns and of the different frequency bands extracted by numerical filtering from the faunal record with the same components modulating the insolation curve provided an astronomic calibration of the sedimentary record and, consequently, a precise age for all the calcareous plankton bioevents recognized throughout the studied interval.